THE ROLE OF TEACHERS AND STUDENTS IS TRANSFORMING NONCOMMUNICATIVE LANGUAGE TEACHING - Saydivaliyeva, Barno (Журнал иностранных языков и лингвистики, 2023)
In our article, EFL teaching in Uzbekistan differs in its traditionalism from that in the United States and Great Britain, as it is conducted in different socio-cultural conditions. However, this does not mean that the communicative approach is not used in such a context. For this approach to work well in Uzbekistan, we need to combine it with the traditional grammatical translation method, which is still widely used in Uzbekistan.